PERKEMBANGAN TEKNOLOGI IDENTIFIKASI SERANGGA DARI ZAMAN KE ZAMAN - Indriati, Gusti; Hidayat, Purnama (JURNAL AGRISA, 2023)
Insect classification is carried out using various identification techniques, namely conventional and modern. Accurate identification techniques for insect species are an important key in determining effective pest control measures. Insect classification and insect identification methods are interrelated because proper classification is a necessary basis for effective identification methods. The development of insect classification based on time is divided into several stages, namely: Pre-Linnean Era, Linnean Era, Darwinian Era, and Hennigian Era. The traditional method of identifying pest insects is done manually to recognize and classify pest insects based on morphological, anatomical and other characteristics. Although this method tends to be slower and requires a high degree of manual skill, it remains an important basis for taxonomy. Rapid progress in the world of research requires increased quality and speed of time, thus requiring modern and up-to-date insect identification methods such as Next-Generation Squencing (NGS), DNA Barcoding, Computer Vision, Mobile Apps and Citizen Science, and Micro CT Scanning. Supporting the implementation of modern technology requires software development, specialized equipment, and careful validation to ensure accuracy and efficiency as well as human resources. A combination of advanced technology and traditional methods may be the most effective approach in insect taxonomy identification.